Behavioral Variant Frontotemporal Dementia as a Serious Complication of Spontaneous Intracranial Hypotension. Issue 5 (8th March 2018) - Schievink, Wouter I; Maya, M Marcel; Barnard, Zachary R; Moser, Franklin G; Jean-Pierre, Stacey; Waxman, Alan D; Nuño, Miriam
Abstract: BACKGROUND: Behavioral variant frontotemporal dementia (bvFTD) is a devastating early onset dementia. Symptoms of bvFTD may be caused by spontaneous intracranial hypotension (SIH), a treatable disorder, but no comprehensive study of such patients has been reported. OBJECTIVE: To describe detailed characteristics of a large cohort of patients with SIH and symptoms of bvFTD. METHODS: We identified patients with SIH who met clinical criteria for bvFTD. Patients were compared to a cohort of SIH patients without bvFTD. RESULTS: The mean age for the 21 men and 8 women was 52.9 yr (range, 37–65 yr). All 29 patients with bvFTD symptoms had hypersomnolence. Magnetic resonance imaging showed brain sagging in all patients, cerebrospinal fluid (CSF) opening pressure low in about half of patients, but a spinal CSF leak could not be detected in any patient. All patients underwent epidural blood patching, but 26 patients eventually underwent 1 or more surgical procedures. Overall, a good outcome was obtained in 21 patients (72%); 20 (91%) of 22 patients who had not undergone prior Chiari surgery compared to 1 (14%) of 7 patients who did undergo Chiari surgery ( P < .003). Compared to SIH patients without symptoms of bvFTD (n = 547), those with bvFTD symptoms were older, more often male, less often demonstrated CSF leak on spinal imaging, and more often underwent surgery ( P < .02). CONCLUSION: bvFTD in SIH is rare and associated with brain sagging and hypersomnolence. Spinal CSF leaks are rarely detected. bvFTD symptoms are often refractory to the usual percutaneous procedures but most patients can be cured.